The Debate at the Beginning of the 21st Century on the Peopling of the Americas - Miotti, Laura Lucía (2012)
Fil: Miotti, Laura Lucía. División Arqueología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina